Legal Protection of Creditors in Non-Collected Debtors Without Collateral in Koperasi Cahaya Abadi, Kediri District - Sofyetin Atiana (Activa Yuris: Jurnal Hukum, 2023)
This study aims to explain the legal protection for creditors in bad loans Debtors without collateral in the Koperasi Cahaya Abadi, Kediri Regency and settlement of bad credit debtors without collateral in the Koperasi Cahaya Abadi, Kediri Regency. The empirical juridical research method is also called research examining law as a pattern of behavior shown in the application of legal regulations. The empirical juridical approach is carried out by collecting primary data information obtained directly in the field aimed at applying the law and/or resolving bad loans related to bad loans from debtors who have no collateral. Whereas in legally protecting creditors for bad credit from unsecured debtors, it is necessary to have preventive and repressive legal protection measures / get customers / debtors. Meanwhile, reflective legal protection for debtors without collateral, the steps taken by the Cahaya Abadi Cooperative are Rescheduling, Reconditioning Restructuring, and Execution